Brazil : Maternal and Child Health - World Bank (Washington, DC, 2013)
The health care system in Brazil has established the important principle of universal coverage, yet, it faces several key challenges: its expenditure patterns favor the regions that are already better off, and healthier, and, needs to take into account diverse practices, and cultures, in addition to considerations for the weak referral system. The report focuses on the health care system, particularly on enhancing maternal and prenatal health, certain health care interventions, such as immunizations, oral rehydration therapy, and case management. Chapter 1 argues that the major reason for the maternal and child health risks is the concentration of illness and death among the poor : infant mortality rates jump 80-100 percent from the next to lowest income quintile, to the lowest. Several interventions, such as strategies to promote productivity, increase economic opportunities, and enhance maternal education among the poor, could help reduce inequalities. Chapter 2 uses estimates of avoidable child deaths to prioritize health interventions in the country, and, Chapter 3 argues that the federal government programs in women and children's health could be expanded by prioritizing on failed expenditure patterns, improving referral systems, and emphasizing the importance of utilizing nutrition education. Chapter 4 makes policy recommendations on sector goals, suggests basic actions to achieve such goals, and provides measures to improve the quality of care, and evaluation.